Students’ cognitive load in online education, under the lens of learning theories - Marius BĂNUȚ; Daniel ANDRONACHE (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia, 2023)
There is a link between learning theories and online education in the sense that the use of certain e-Tools available in educational platforms could be biased by the epistemological beliefs of the teachers. The complexity of the educational message, in relation to the biased e-Tools selection for the learning task, together with the information processing that derives from the learning activity contributes to the intrinsic cognitive load. In order to optimize this cognitive load that can reach a high and an undesirable level for learning, this article aims to bridge online learning with the main theories of learning and cognitive load theory. The triangulation of these data, based on several sources from the specialized literature, provides an extended picture of the dominant cognitive processes determined by the tools used in the online learning space. This article could represent a source for the theoretical foundation of an online learning instructional design and for placing the online education closer to methodology, rather than technology.